Emphasis As A Linguistic And Stylistic Phenomenon - Денисенко, Надія Валеріївна; Мілько, Наталія Євгенівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article focuses on a complex study of the peculiarities of English emphasis rendering in Ukrainian fiction translations. The research is based on the contrastive analysis of emphasis in the systems of the English and Ukrainian languages in the works by English and American writers and their translations into Ukrainian. The work deals with the problems of translating English emphasis and their combinations, depending on their communicative and pragmatic functions in different communication types of utterances. A classification of the types and kinds of English and Ukrainian emphasis is made. Conditions and peculiarities of translating emphatic means are found out and compared in English-Ukrainiаn translations.